2014
DOI: 10.1093/infdis/jiu318
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward Poliomyelitis Eradication in Nigeria

Abstract: Efforts to interrupt transmission remain impeded by poor SIA implementation in localized areas, anti-polio vaccine sentiment, and limited access to vaccinate children because of insecurity. Sustained improvement in SIA quality, surveillance, and outbreak response and special strategies in security-compromised areas are needed to interrupt WPV transmission in 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Table 2 presents five identified scientific publications 30-33,35 reporting the evaluation of interventions on newborn health already operational in Nigeria. There were also two publications 34,36 that implemented an intervention to generate evidence to improve newborn health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 presents five identified scientific publications 30-33,35 reporting the evaluation of interventions on newborn health already operational in Nigeria. There were also two publications 34,36 that implemented an intervention to generate evidence to improve newborn health.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 76 publications yielded in category 2, 7(9.2%) 30-36 satisfied the study inclusion criteria regarding newborn health and were selected (Table 2), while of the 249 publication from category 3, only 3 (1.2%) 37-39 met the study inclusion criteria regarding child health and were selected (Table 3). The flowchart of the study selection procedure is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods may be used to identify polio high-risk districts in a given country [911]. The most common information used has included population immunity, sensitivity of disease surveillance, and insecurity.…”
Section: Methodsmentioning
confidence: 99%
“…As we approach WPV eradication and manage OPV cessation, the vaccination of subpopulations emerges as critical for success. Undervaccinated subpopulations can sustain transmission and pose challenges because of a confluence of factors [11,12] related to political circumstances (including poor program performance, low vaccination coverage, poor surveillance, and/ or poor data quality), conditions that favor intense fecal-oral poliovirus transmission and correlate with low socioeconomic status (including poor sanitary and hygienic conditions, high birth rates and crowding, poor nutrition, poverty, and high exposure to pathogens that interfere with vaccine response), and/or limited access (including immigrants, displaced populations, and populations in violent, insecure, or remote areas) [13][14][15][16][17][18][19][20][21]. However, other subpopulations also emerge as important, including those in countries with sufficient access to vaccine who refuse immunization [22][23][24][25][26].…”
mentioning
confidence: 99%